Prevalence of Rotavirus Genogroup A and Norovirus Genogroup II in Bassaseachic Falls National Park Surface Waters in Chihuahua, Mexico - Delgado Gardea, María del Carmen Elizabeth; Tamez Guerra, Patricia; Gómez Flores, Ricardo Alberto; Mendieta Mendoza, Aurora; Zavala Diaz de la Serna, Francisco Javier; Contreras Cordero, Juan Francisco; Erosa de la Vega, Gilberto; Pérez Recoder, María; Sánchez Ramírez, Blanca; González Horta, Carmen; Infante Ramírez, María del Rocío (2017)
Abstract: In areas lacking potable water treatment, drinking contaminated water may represent a public health threat. In addition to enteropathogenic bacteria and parasites, fecal contamination in water environments is associated with the transmission of enteric viruses and other causal agents of infectious disease. Rotavirus and norovirus are the main enteric viral agents responsible for diarrheic outbreaks. The aim of the present study was to detect seasonal variation of rotavirus and norovirus in the surface water at Bassaseachic Falls National Park during 2013. Rivers and streams within and nearby this park were sampled once in each season during 2013. Viral concentration was carried out by a handmade ﬁltration equipment, using a commercial electropositive membrane coupled with the virus absortion elution technique (VIRADEL©). Detection of rotavirus and norovirus was performed by SYBR Green reverse transcription-real time polymerase chain reaction (SYBR GREEN© RT-qPCR) analyses. Norovirus genogroup II was detected in samples collected in June and October 2013. Inthecaseofrotavirus,genogroupAwasdetectedinMarchandJune. Thepresenceofrotavirus and norovirus was related to viral acute diarrhea in children less than ﬁve years of age, who were inhabiting the sampled areas. This may indicates that the contaminated water was potentially a risk factor for regional diarrheic outbreaks. Keywords: norovirus; rotavirus; surface water; VIRADEL; virus detection; environment